“HIS LOYALTY IS REPUTED”: POLITICAL ACTIVITY OF NAIB OF DERBENT IMAM KULI-BEK - Magaramov, Sarafutdin Arifovic (History, Archeology and Ethnography of the Caucasus, 2022)
The accession of Derbent to the Russian Empire as a result of the Persian campaign of Peter the Great and being the part of it until 1735 is one of the important milestones in the centuries-old history of Derbent. The peaceful process of joining the city to the empire was greatly facilitated by the political position and activities of the city ruler in the person of Naib Imam Kuli-bek, who decided not to resist the imperial troops and peacefully surrender the city to Tsar Peter the Great. Being approved by Peter I in the same position, Naib developed an active political activity with the imperial authorities, demonstrated timely concern for protecting the city from attacks by mountaineers and providing food for the townspeople, shared managerial and judicial functions with the Russian commandant A.T. Junger. The study of the political activities of Naib Imam Kuli-bek, the nature of his relationship with the Russian central and regional authorities makes it possible to deepen and expand historical knowledge about the events in Derbent, and in the Eastern Caucasus as a whole, related to imperial policy in the region in the first third of the 18th century. However, a special study of the activities of Naib Imam Kuli-bek in domestic historiography has not yet been undertaken, which is the reason for the relevance of the present study. The article aims to analyze the activities of the Naib in building relations with the new imperial government, integrating Derbent into the political, legal and economic space of the Russian Empire; show cases demonstrating loyalty (loyal speech, offering a key, honoring the monarch, a visit to the imperial court) on the part of the Naib, and power and favor (approval in office, rank, gifts, awards) on the part of sovereigns. The study has been prepared on the basis of an analysis of available works and a wide range of documentary data from the collections of federal and regional archives, a significant part of which is being introduced into science for the first time.
Keywords: Peter the Great; Persian Campaign of 1722-1723; Derbent; Naib Imam Kuli-bek; pro-Russian activity; investiture